Reforming Global Tax Rules And Standards For The Digital Economy - Mokhinur Bahramovna Bakhramova (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2026)
This paper investigates options for reforming global tax rules and standards to address challenges from the digital economy. Analysis of European Union, United States, China and India taxation practices reveals a spectrum of policy measures balancing revenue rights, investment competitiveness, and compliance costs. Findings emphasize the need to update concepts like nexus and profit allocation, while retaining coherence, certainty and fairness. Consensus-based multilateral solutions can prevent damaging unilateral taxes. For developing countries, gradual reforms aligned with international standards are recommended to sustain digital economy growth.